1999
DOI: 10.1017/s0950268899002411
|View full text |Cite
|
Sign up to set email alerts
|

Sampling considerations for herd-level measurement of faecal Escherichia coli antimicrobial resistance in finisher pigs

Abstract: The objective of this study was to determine the most efficient means of sampling faeces of finisher pigs for accurate and precise farm-level estimates of antimicrobial resistance among faecal Escherichia coli. Resistance to tetracycline and gentamicin of 8250 isolates of E. coli from 55 finisher pigs on one farm was measured with a hydrophobic grid membrane filter method. The between-pig, within-pen component of variance in resistance was large (97.5%), while between-pen, within-room and between-room componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
7
23
0
Order By: Relevance
“…Dunlop et al (1999) attributed much of the variability in E. coli AR prevalence within each farm to within-pig and within-pen differences rather than between-pen, within-room, and between-room components. However, they examined individual pig samples, and ours were composites collected across pens within production group.…”
Section: Discussionmentioning
confidence: 99%
“…Dunlop et al (1999) attributed much of the variability in E. coli AR prevalence within each farm to within-pig and within-pen differences rather than between-pen, within-room, and between-room components. However, they examined individual pig samples, and ours were composites collected across pens within production group.…”
Section: Discussionmentioning
confidence: 99%
“…One study of antimicrobial resistance in swine found that the precision of resistance estimates did not improve noticeably when more than 5 colonies were selected per swine fecal sample. 2 Another study demonstrated clustering of antimicrobial resistant phenotypes among isolates from feedlot cattle fecal samples and suggested that fewer than 5 isolates per sample is a reasonable guideline. 9 Wagner et al 9 suggested increasing the number of fecal samples, if possible, to increase the total number of isolates being tested for susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…In many previous investigations, the clustered nature of data has often been ignored in the data analysis. Dunlop et al 15 considered the variation in tetracycline and gentamicin resistance between pigs within pens, the variance between pens within rooms, and between rooms within a farm for sampling consideration. In the single farm included in that study, the between-pig within-pen variation constituted the overwhelming majority of the variance (97.5%).…”
Section: Subtherapeutic Chlortetracycline and Resistance In The Aerobmentioning
confidence: 99%